Influence of ABCB1 3435C>T polymorphism on methotrexate safety in patients with psoriasis - Alexey A. Kubanov; Anastasiia V. Asoskova; Michael S. Zastrozhin; Zhannet A. Sozaeva; Dmitry A. Sychev (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Background. Methotrexate is a highly effective systemic treatment for moderate to severe psoriasis, but drug toxicity may limit its use. Recent evidence suggests that it is necessary to take into account the individual characteristics of methotrexate pharmacokinetics, which are determined by the presence of polymorphisms of genes encoding methotrexate carrier proteins, to predict the risk of methotrexate-induced toxicity. Aims. The research aim is the assessment of associations of ABCB1 rs1045642 (3435CT) polymorphism with methotrexate safety for the patients with moderate and severe forms of psoriasis. Materials and methods. The study included 75 patients diagnosed with psoriasis treated with methotrexate during 21 day. Data on adverse drug reactions were collected using a clinically structured questionnaire, complete and biochemical blood tests, and urinalysis. The severity of adverse drug reactions was assessed using visual analog scales and the CTCAE toxicity scale. The severity of gastrointestinal ADR was assessed using the GSRS questionnaire. Genotyping was carried out by real-time PCR. Results. The gastrointestinal toxicity was detected in 38 patients (50.67%). The mean GSRS score was 7.97 9.18. Analysis of differences in the incidence of adverse drug reactions showed the presence of statistically significant differences in the frequency of adverse drug reactions in the gastrointestinal tract: the toxic effect of methotrexate was more often observed in carriers of the T allele of the ABCB1 rs1045642 polymorphism (3435CT), (CC 2 (14.3%), TC 18 (52.9%), TT 18 (66.7%), p = 0.006). Binomial regression demonstrated the presence of a statistically significant effect of the rs1045642 SNP polymorphism of the ABCB1 gene on the incidence of ADR from the gastrointestinal tract (OR = 8.64, p = 0.008). Conclusions. An association of ABCB1 rs1045642 SNP with the safety of gastrointestinal methotrexate therapy in patients with moderate and severe forms of psoriasis was revealed. The data obtained can be used to personalize the prescription of methotrexate to patients with psoriasis.